PENGEMBANGAN BUKU PANDUAN GURU PEMBIMBING KHUSUS UNTUK MENINGKATKAN KOMPETENSI DALAM MERANCANG PROGRAM PEMBELAJARAN INDIVIDUAL DI SEKOLAH DASAR - Emiliyana; Rangga Firudaus; Muhammad Nurwahidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research on the development of a guidebook for special guidance teachers to improve their competence in implementing individual learning programs for students with special needs in elementary schools aims to develop a guidebook for special guidance teachers. This study used the Research and Development method, while the development model used was ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research subjects were special guidance teachers at the Miryam Foundation elementary school. Data collection used instruments in the form of interviews, validation questionnaires, limited trials, and extensive trials. The results of this study indicate that the guidebook developed is valid, practical, and effective. Expert validation obtained a score of 92%, and the trial results showed an increase in the understanding and skills of GPK in compiling and implementing Individual Educational Program. This study concluded that the developed guidebook is suitable for use as professional reference material for GPK in elementary schools.